Model Pengendalian Internal Berbasis Sarbanes-Oxley Act dan Keandalan Pelaporan Keuangan (Studi Internal Audit Pada Perusahaan Publik di Indonesia) - Syahril Djaddang; Shanti Lysandra (Jurnal Ekonomi dan Bisnis, 2015)
This study focus on internal control application based on the Sarbanes-Oxley Act. The research objective is to examine the impact of Sarbanes-Oxley Act implementation and the financial reporting reliability toward audit quality and audit opinion. The research is conducted on public companies implementing Sarbanes- Oxley Act in Indonesia. The internal audit section in the companies are used as respondents. Based on questionnaires distributed, there were 35 samples of public companies used in this research. This study employs WarpPLS to handle the SEM model in testing the hypotheses and multigroup analysis to conduct the sensitivity analysis. The research’s results showed that application of Sarbanes-Oxley Act based internal control and financial reporting reliability are positively affect the audit opinions and directly influence the audit quality. However, the independent auditor's opinion is not a moderating variables between other variables. The research results are expected to be used as considerations by the companies in implementation of Sarbanes-Oxley Act based internal control.